The X‐ray crystal structure of Shewanella oneidensis OmcA reveals new insight at the microbe–mineral interface. Issue 10 (18th April 2014) - Edwards, Marcus J.; Baiden, Nanakow A.; Johs, Alexander; Tomanicek, Stephen J.; Liang, Liyuan; Shi, Liang; Fredrickson, Jim K.; Zachara, John M.; Gates, Andrew J.; Butt, Julea N.; Richardson, David J.; Clarke, Thomas A.
Abstract : The X‐ray crystal structure of Shewanella oneidensis OmcA, an extracellular decaheme cytochrome involved in mineral reduction, was solved to a resolution of 2.7 Å. The four OmcA molecules in the asymmetric unit are arranged so the minimum distance between heme 5 on adjacent OmcA monomers is 9 Å, indicative of a transient OmcA dimer capable of intermolecular electron transfer. A previously identified hematite binding motif was identified near heme 10, forming a hydroxylated surface that would bring a heme 10 electron egress site to ∼10 Å of a mineral surface. Abstract : We have resolved the crystal structure of the decaheme OmcA to 2.7 Å resolution. A proposed heme binding motif is identified around heme 10. Heme 5 is proposed as a site for intermolecular electron transfer.